Gender, Social, Cultural Injustice in the Short Story “Di Atas Tanah Retak” and the Lesson Plan - Sulistyaningrum, Caecilia Fani; Dewi, Novita (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to describe: 1) gender, social and cultural injustice in the short story "Di Atas Tanah Retak" by Tasia Sugiyanto for the aspects of (a) the influence of local culture and myths in the short story, (b) gender and social injustice, (c) the influence of questions and economy on the life of the central character, (d) symbolism and meaning of hanging in the short story, (e) psychological impact on the character of the character; 2) the implementation plan for learning in high school using the process skills approach, copying assignment techniques, and practice techniques through Google Form media. This study uses a library method so that both literary studies and learning implementation plans are based on literature studies. The collection of short story data was carried out using observation guidelines to obtain research data. The data were analyzed using a thematic approach based on a structural approach that combines intrinsic elements, namely characters and characterizations with extrinsic elements, namely gender, social, and culture that underlie the short story. A checklist is used to validate the data collected and validate the results of data analysis using time triangulation techniques. Research results: 1) gender, social and cultural injustice in the short story "Di Atas Tanah Cracks' as a result of the influence of local culture and myths in short stories, the presence of gender and social injustice, the influence of questions and economics on the lives of central characters, the symbolism and meaning of hanging in short stories, and the psychological impact on character characters; 2) the learning implementation plan in high school that uses a process skills approach, copying assignment techniques, and practice techniques through Google Form media involves 17 core activities.